Formulation, Characterization, and In Vitro Drug Release Study of β-Cyclodextrin-Based Smart Hydrogels - Muhammad Suhail; Quoc Lam Vu; Pao-Chu Wu (Gels, 2022)
In this study, novel pH-responsive polymeric β-cyclodextrin-graft-poly(acrylic acid/itaconic acid) hydrogels were fabricated by the free radical polymerization technique. Various concentrations of β-cyclodextrin, acrylic acid, and itaconic acid were crosslinked by ethylene glycol dimethacrylate in the presence of ammonium persulfate. The crosslinked hydrogels were used for the controlled delivery of theophylline. Loading of theophylline was conducted by the absorption and diffusion method. The fabricated network of hydrogel was evaluated by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), X-ray diffractometry (XRD), and scanning electron microscopy (SEM). The crosslinking among hydrogel contents and drug loading by the fabricated hydrogel were confirmed by FTIR analysis, while TGA indicated a high thermal stability of the prepared hydrogel as compared to pure β-cyclodextrin and itaconic acid. The high thermal stability of the developed hydrogel indicated an increase in the thermal stability of β-cyclodextrin and itaconic acid after crosslinking. Similarly, a decrease in crystallinity of β-cyclodextrin and itaconic acid was observed after crosslinking, as evaluated by XRD analysis. SEM revealed an irregular and hard surface of the prepared hydrogel, which may be correlated with strong crosslinking among hydrogel contents. Crosslinked insoluble and uncrosslinked soluble fractions of hydrogel were evaluated by sol–gel analysis. An increase in gel fraction was seen with the increase in compositions of hydrogel contents, while a decrease in sol fraction was observed. Dynamic swelling and dissolution studies were performed in three various buffer solutions of pH 1.2, 4.6, and 7.4, respectively. Maximum swelling and drug release were observed at higher pH values as compared to the lower pH value due to the deprotonation and protonation of functional groups of the hydrogel contents; thus, the pH-sensitive nature of the fabricated hydrogel was demonstrated. Likewise, water penetration capability and polymer volume were evaluated by porosity and polymer volume studies. Increased incorporation of β-cyclodextrin, acrylic acid, and itaconic acid led to an increase in swelling, drug release, drug loading, and porosity of the fabricated hydrogel, whereas a decrease was detected with the increasing concentration of ethylene glycol dimethacrylate. Conclusively, the prepared hydrogel could be employed as a suitable and promising carrier for the controlled release of theophylline.